Morphology and distribution of bedforms in the Amazon River channel in Jatuarana: implications for the rock record? - Galeazzi, Cristiano Padalino (2016)
Development of large river facies models is hampered by the lack of observations from active large river systems, especially considering bedforms that never emerge throughout the year, which account for the majority of the channel. To overcome the scarcity of data, and observe what happens beneath tens of meters of water, this research presents a MBES image from a selected area in the Upper Amazon River, in northern Brazil. The image revealed the presence of two depositional systems, the thalweg and a bank attached bar. The channel is predominantly covered by sand, that forms very large compound dunes in the deepest parts of the channel, such as the thalweg and the base of the bar, and smaller dunes in shallower areas, such as the bar top. The large compound dunes reach up to 10,4 m of height and 300 m of wavelength, presenting generally low angles in their lee sides and grains of coarse sand that may present granules. Three types of compound dunes were identified, Compound Barchanoid and Sinuous Dunes, located in the thalweg, and Compound Oblique Dunes, located in the base of the bar. All compound dunes present very large dune heights, but only the barchanoid presents steep lee angles that reached avalanche slopes. Superimposed dunes cover a large part or most of the lee sides in all types of compound dunes, whenever the lee angle is below 10°. In contrast, the shallower areas are composed by smaller simple dunes that present high lee angles and are constituted by grains of medium sand size. Sedimentary structures were inferred for every bedform described in the channel. The recognition of the differences between the deep and shallow channel may allow to improve facies models for large river and allow to identify these features in the rock record.